PSYCHOLOGICAL FEATURES OF AMBIVALENCE IN YOUTH’S PERCEPTION OF PROFESSIONAL SUCCESS - Попелюшко, Роман; Ванеєва, Катерина (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
This article examines the psychological features of ambivalence in young people’s perception of professional success. The aim of the study is to identify the psychological characteristics of young people’s ambivalent attitudes toward professional success. The objectives include: conducting a theoretical review of ambivalence in attitudes toward professional success; experimentally studying young people’s ideas about professional success, along with features of the family environment and gender attitudes; and determining and describing the relationships between ambivalent attitudes toward success and socio-psychological factors, particularly family cohesion, adaptability, and stereotypical beliefs. The methodological basis of the study consists of theoretical methods involving analysis and synthesis of scientific literature on achievement psychology, ambivalence, and the influence of family factors. The empirical methods include the use of the FACES-III questionnaire, ASI, and AMI scales. Results. Only respondents under 35 years old (N = 39) from the total sample (N = 64; women = 22, men = 17) were included in the analysis. The data indicate a pragmatization of the concept of success (success = stability; success during wartime has a different meaning), as well as egalitarian gender attitudes. FACES-III revealed dominance of the «Separated–Flexible» and «Connected–Flexible» profiles, indicating a supportive family environment. ASI and AMI scores fall within moderate ranges. Conclusions. It was established that ambivalence in the perception of professional success manifests as a combination of striving for achievement and fears of possible consequences. The intensity of this ambivalence is softened by family support and egalitarian views. The practical significance lies in developing support programs that help transform ambivalence into a resource for development. The results emphasize the importance of working with individuals’ internal conflicts. Such interventions promote strengthening motivation and increasing psychological resilience. Future research prospects involve considering the fact that participants were employees of an international company, which influenced the results in the context of the global organizations’ corporate culture. Further studies should focus on the experiences of employees in Ukrainian companies to compare cultural and organizational effects on ambivalence in the perception of professional success.